SISTEM PEMILU ONLINE BERBASIS PROTOKOL TWO CENTRAL FACILITIES - Sikki, Muhammad Ilyas (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2013)
An election is an simple example of a scenario where security and confidentiality of data  between parties is critical. General election system that used in Indonesia as it long still use conventional trick that evokes a lot of problem as elector of double, voice distension and another fault and also long time for vote count. This conventional trick also require big costs and resources. To settle that thing, one of solution which can be done is use electronic voting ( e-voting ) with arrange general election system online  that building to use a safe protocol.System that is made has default pock secure voting reguirements to get settles and secure security each threat which will happen. One of protocol which can accomplish partly criterion default secure voting reguirements  and has security zoom that passably is Two Central Facilities Protocol , where consisting of Central Legitimazation Agency  (CLA) for elector validation and Central Tabulating Facility (CTF) for vote count.